The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2012
DOI: 10.1186/1479-5876-10-149
|View full text |Cite
|
Sign up to set email alerts
|

Upregulation of SATB1 is associated with the development and progression of glioma

Abstract: BackgroundSpecial AT-rich sequence-binding protein-1 (SATB1) has been reported to be expressed in several human cancers and may have malignant potential. This study was aimed at investigating the expression and potential role of SATB1 in human glioma.MethodThe relationship between SATB1 expression, clinicopathological parameters, Ki67 expression and MGMT promoter methylation status was evaluated, and the prognostic value of SATB1 expression in patients with gliomas was analyzed. SATB1-specific shRNA sequences … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
56
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 54 publications
(64 citation statements)
references
References 35 publications
7
56
1
Order By: Relevance
“…In line with these observations, Wang et al reported that deficiency in SATB1 expression in Sézary cells caused resistance to apoptosis [41]. However, Chu et al found that downregulation of SATB1 expression was responsible for the initiation of active cell death [42].…”
supporting
confidence: 51%
“…In line with these observations, Wang et al reported that deficiency in SATB1 expression in Sézary cells caused resistance to apoptosis [41]. However, Chu et al found that downregulation of SATB1 expression was responsible for the initiation of active cell death [42].…”
supporting
confidence: 51%
“…Epigenetic modifications and dynamic changes in chromatin organization by organizer proteins have recently been shown to play an instrumental role in regulating cancer-promoting genes [34,35]. Aberrant expression of SATB1 mRNA and protein has been shown to promote growth and metastasis of various neoplasms [10][11][12][13][14][15][16][17][18][19][20][21][22][23][24][25][26]. The main and most quoted role of SATB1 is chromatin organization and functioning as a global regulator of gene expression, among others during cancer development (e.g.…”
Section: Discussionmentioning
confidence: 99%
“…SATB1 as a MAR-binding protein regulates the genes by folding chromatin into loop domain [8]. It was found to regulate gene expression in thymocytes and pre B-cells [9], but recent studies have shown that SATB1 promotes tumor growth and metastasis through chromatin gene recombination in many neoplasms such as breast, gastrointestinal tract (predominantly colorectal region), liver, laryngeal, lung, thyroid, urinary bladder, ovarian and prostate cancers, melanomas, osteosarcomas, gliomas and some types of leukemias [10][11][12][13][14][15][16][17][18][19][20][21][22][23][24][25][26]. Furthermore, except SATB1 involvement in tumor progression by its mRNA and protein overexpression in some cancers, e.g.…”
Section: Introductionmentioning
confidence: 99%
“…8 The role of SATB1 in development of multiple cancers has been extensively studied. 7 Aberrant SATB1 expression has been shown to be associated with multiple cancers including liver cancer, 9 ovarian cancer, 10 Glioma, 11 gastric cancer. 12,13 Recently, potential role of SATB1 in colorectal cancer development has been studied.…”
Section: Introductionmentioning
confidence: 99%